Under the Umbrella: Nuclear Crises, Extended Deterrence, and Public Opinion. (November 2022) - Allison, David M.; Herzog, Stephen; Ko, Jiyoung
How robust is public support for extended nuclear deterrence in patron and client states? Recent studies have improved scholarly understanding of US public opinion about nuclear weapon use against non-nuclear adversaries. Yet, there is limited knowledge of public attitudes regarding retaliation for nuclear strikes against US allies. We develop a theoretical typology of nuclear crises and investigate this phenomenon with a novel survey experiment ( n = 6, 623). Americans, Japanese, and South Koreans viewed realistic emergency alert messages about a most-likely case for nuclear retaliation: a North Korean missile attack on a US ally protected by the nuclear umbrella. Support for nuclear retaliation is low in all three countries, with important cross-national differences. Favorability increases with North Korean nuclear first-use, but it remains limited nonetheless. Surprisingly, US "tripwire" troop casualties do not increase Americans' demands for nuclear retaliation. These findings have important implications for the study of nuclear crises and practice of extended deterrence.